Biofuels Production from Biomass by Thermochemical Conversion Technologies. (8th April 2012) - Verma, M.; Godbout, S.; Brar, S. K.; Solomatnikova, O.; Lemay, S. P.; Larouche, J. P.
Abstract : Agricultural biomass as an energy resource has several environmental and economical advantages and has potential to substantially contribute to present days' fuel demands. Currently, thermochemical processes for agricultural biomass to energy transformation seem promising and feasible. The relative advantage of thermochemical conversion over others is due to higher productivity and compatibility with existing infrastructure facilities. However, the majority of these processes are still under development phase and trying to secure a market share due to various challenges, right from suitable infrastructure, raw material, technical limitations, government policies, and social acceptance. The knowledge at hand suggests that biomass can become a sustainable and major contributor to the current energy demands, if research and development are encouraged in the field of thermochemical conversion for various agricultural biomass types. This paper intends to explore the physical and chemical characteristics of biofuel substitutes of fossil fuels, potential biomass sources, and process parameters for thermochemical conversion.